Transcriptome profiling of pumpkin (Cucurbita moschata Duch.) leaves infected with powdery mildew. - Wei-Li Guo (PLoS ONE, 2018)
Cucurbit powdery mildew (PM) is one of the most severe fungal diseases, but the molecular mechanisms underlying PM resistance remain largely unknown, especially in pumpkin (Cucurbita moschata Duch.). The goal of this study was to identify gene expression differences in PM-treated plants (harvested at 24 h and 48 h after inoculation) and untreated (control) plants of inbred line "112-2" using RNA sequencing (RNA-Seq). The inbred line "112-2" has been purified over 8 consecutive generations of self-pollination and shows high resistance to PM. More than 7600 transcripts were examined in pumpkin leaves, and 3129 and 3080 differentially expressed genes (DEGs) were identified in inbred line "112-2" at 24 and 48 hours post inoculation (hpi), respectively. Based on the KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway database and GO (Gene Ontology) database, a complex regulatory network for PM resistance that may involve hormone signal transduction pathways, transcription factors and defense responses was revealed at the transcription level. In addition, the expression profiles of 16 selected genes were analyzed using quantitative RT-PCR. Among these genes, the transcript levels of 6 DEGs, including bHLH87 (Basic Helix-loop-helix transcription factor), ERF014 (Ethylene response factor), WRKY21 (WRKY domain), HSF (heat stress transcription factor A), MLO3 (Mildew Locus O), and SGT1 (Suppressor of G-Two Allele of Skp1), in PM-resistant "112-2" were found to be significantly up- or down-regulated both before 9 hpi and at 24 hpi or 48 hpi; this behavior differed from that observed in the PM-susceptible material (cultivar "Jiujiangjiaoding"). The transcriptome data provide novel insights into the response of Cucurbita moschata to PM stress and are expected to be highly useful for dissecting PM defense mechanisms in this major vegetable and for improving pumpkin breeding with enhanced resistance to PM.